The impact of using a protective mask on the occurrence of maskne (mask acne) during the Covid-19 pandemic - Jakubowska, Eliza; Nowak, Tomasz; Łazicka, Patrycja; Jasińska, Joanna; Miziniak, Marta; Karolak, Aleksandra (Journal of Education, Health and Sport, 2023)
Introduction The COVID-19 pandemic has led to a increase in the use of personal protective equipment (PPE). The term "maskne" was coined to describe acne caused by long-term wearing of a mask. It is a type of mechanical acne caused by the pressure and friction of the mask material against the skin. Although it’s prevalance is not well known, the maskne problem is becoming more and more significant. Aim of study The aim of the study is to assess the prevalence and factors affecting the occurrence of mask acne. Materials and methods This cross-sectional study was conducted after the end of the COVID-19 pandemic among 148 residents of Poland. The results were obtained thanks to a self-conducted questionnaire distributed in both electronic and traditional form. Results In total, 148 participants took part in the study. 106 (71.6%) were women and 42 (28.4%) were men, with the dominant age group being 26-40, 70 (47.3%). Most participants wore a mask seven days a week, 62 (41.9%), four to eight hours a day, 70 (47.3%). Surgical masks were the most frequently used masks – 60 (40.5%). Ninety (60.8%) participants had no prior facial skin disease. Only 58 (39.2%) of participants had prior facial skin lesions. Of these, acne vulgaris was the most common, 48 (82.8%), followed by rosacea, 6 (10.4%), and psoriasis, 4 (6.8%). Fifty-three people (35.8%) who had facial acne before the pandemic said their acne got worse. Conclusions This study showed a significant association between the worsening of existing acne and frequent and long-term use of face masks. Therefore, certain measures should be taken to prevent the formation of new acne or the aggravation of existing acne while maintaining protection with face masks, especially for those working in the healthcare sector.